Urban Sustainability and Resilience Governance: Review from The Perspective of Climate Change Adaptation And Disaster Risk Reduction - Novi Maulida Ni'mah; Bambang Hari Wibisono; Muhammad Sani Roychansyah (The Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
The imperative of ‘making cities resilient and sustainable’ necessitates cities to develop adaptation concepts and practices in response to the uncertainty, rapid change, and complexity of urban areas. A new concept of governance that can answer the challenges of contemporary urban development and ensure long-term sustainable development is required. This study aimed to identify the general framework of adaptive urban governance by review, elaboration, and analysis of documents, in this case, scientific articles that discuss urban governance specifically related to climate change adaptation (CCA) and disaster risk reduction (DRR). The results of this study include an overview of governance approaches appearing in the literature on CCA and DRR, which was parsed down to the adaptive and anticipatory approaches. Adaptive governance requires the principle of flexibility applied in the management cycle in policy formulation, while anticipatory governance requires the principle of proactivity with the application of future foresight in policy formulation. The dimension of governance consists of process/mechanism (risk management) and capacity (technical, institutional, financial, and human capacity). Some challenges in building good governance based on an adaptive approach are encouraging community involvement, increasing local government capacities, and building integration between actors, networks, and collaborations. Abstrak. Dalam menjadikan suatu kota tangguh dan berkelanjutan, kota diharuskan untuk mengembangkan konsep dan praktik adaptasi dalam menanggapi ketidakpastian, perubahan yang cepat, dan kompleksitas kawasan perkotaan. Diperlukan konsep tata kelola baru yang dapat menjawab tantangan pembangunan perkotaan kontemporer dan memastikan pembangunan berkelanjutan jangka panjang. Penelitian ini bertujuan untuk mengidentifikasi kerangka umum tata kelola kota adaptif dengan metode review, elaborasi, dan analisis dokumen, dalam hal ini artikel ilmiah yang membahas tentang tata kelola kota secara khusus terkait dengan adaptasi perubahan iklim (CCA) dan pengurangan risiko bencana (PRB). Hasil penelitian ini meliputi gambaran pendekatan tata kelola yang muncul dalam literatur CCA dan PRB, yang diuraikan menjadi pendekatan adaptif dan antisipatif. Tata kelola adaptif membutuhkan prinsip fleksibilitas yang diterapkan dalam siklus pengelolaan dalam perumusan kebijakan, sedangkan tata kelola antisipatif membutuhkan prinsip proaktif dengan penerapan pandangan jauh ke depan dalam perumusan kebijakan. Dimensi tata kelola terdiri dari proses / mekanisme (manajemen risiko) dan kapasitas (teknis, kelembagaan, keuangan, dan kapasitas manusia). Beberapa tantangan dalam membangun tata kelola pemerintahan yang baik berdasarkan pendekatan adaptif adalah mendorong keterlibatan masyarakat, meningkatkan kapasitas pemerintah daerah, dan membangun integrasi antar aktor, jaringan, dan kolaborasi. Kata kunci: pendekatan tata kelola; tata kelola kota; pembangunan berkelanjutan; ketahanan; kerangka konseptual.